THE HISTORY OF POLITICAL RELATIONS OF SULTAN TAKASH WITH THE SELJUQS OF IRAQ AND THE ABBASID CALIPHATE - Tolibjonov Azizjon Tolibjonovich (TARIXIY TADQIQOTLAR, 2026)
This article analyzes the complex military-political situation that emerged in the Near and Middle East during the last quarter of the 12th century, specifically focusing on the decline of the Iraq Seljuq state and the transformation of the Anushteginid-Khwarazmian state into a regional hegemon. The research elucidates the weakening of central authority during the reigns of Sultan Arslan and Sultan Tughril III, the political ambitions of the Atabegs of Azerbaijan (Ildenizids) and the Abbasid Caliph al-Nasir, and demonstrates how Khwarazmshah Takash capitalized on these conflicts to subjugate Persian Iraq (al-Iraq al-Ajam). The author provides a scholarly assessment of the struggle for independence by the last representative of the Iraq Seljuqs, Sultan Tughril III, his tragic demise, and the strategic and diplomatic maneuvers employed by the Khwarazmshah to expand the western frontiers of the empire.